Pemodelan Alat Penghitung Jumlah Penumpang Kereta Berbasis Mikrokontroler Atmega 2560 - Wirawan, Willy Artha; Aghastya, Adya; Lailya, Alvi Lutfyani (Politeknik Perkeretaapian Indonesia Madiun, 2018)
Prambanan Ekspres is a mode of transportation with 3500-5000 passengers per day, with a system of choosing its own seat and train. However, the lack of information on the number of passengers on each train causes several trains to build up. It is necessary to hold an innovation to improve the quality of facilities, comfort and service by making a model of the number of passengers based on the ATMega2560 microcontroller. The stages of this research include observation, design of planning tools, testing tools, taking data, and analyzing the results of research on the number of passengers. Based on the results of testing the tools and research data, it can be concluded that the accuracy of the equipment ranges from 85% to a minimum feasible limit of 60%. Then the model for detecting passengers is above the average eligibility